Evaluating the Localization for E-Learning Website: Case Study in Universiti Malaysia Sabah - Baharum A.; Ismail R.; Fabeil N.F.; Fatah N.S.A.; Tanalol S.H.; Zain N.H.M.; Hanapi R. (Institute of Electrical and Electronics Engineers Inc., 2023)
E-learning; Web Design; Websites; evaluation; Interface designs; Localization; Malaysia; Social acceptance; User interaction; User interface designs; Web objects; User interfaces